P264 Telephone consultations for patients with newly diagnosed low risk lung nodules. (15th November 2017) - Kennedy, MPT; Rodger, KA; Robson, JM; Paramasivam, E; Callister, MEJ
Abstract : Introduction: Lung nodules are a common incidental finding on chest imaging. Their identification on CXR or CT thorax is a common trigger for referral to the lung cancer MDT. Low risk nodules (<8 mm diameter, <300 mm 3 volume, or <10% risk of malignancy on Brock Model) do not require urgent intervention, but may require CT surveillance. These patients, however, are usually aware that they have been referred as "suspected cancer" and require prompt reassurance. In Leeds Teaching Hospitals, patients with low risk nodules were previously brought to lung cancer fast-track clinics for initial consultation. In 2016, we introduced 10 min telephone appointments for patients with new lung nodules, followed by a letter and an information leaflet to the patient. The aim is to improve access to fast-track appointments for patients with a CT scan showing suspected cancer, while allowing patients with low risk lung nodules to receive reassurance sooner and with less inconvenience. We aim to assess the impact of this service on access to fast-track clinics and patient experience. Methods: Patients with new low risk pulmonary nodules were identified from MDT records. We sent surveys to the most recent 24 patients that attended fast-track clinics and 24 patients that had received telephone appointments. Results: During the first three months of the Leeds Pulmonary Nodule Service, a mean of 6 patients per week received telephone consultations, projecting to 325 patients per year. This improved capacity in the fast-track clinic by 4 new patient appointments per week, equivalent to 200 per year. The survey response rate was 13 (54.1%) from fast-track patients and 14 (58.3%) from telephone patients; Table 1. Discussion: The Leeds Pulmonary Nodule Service has led to increased availability of fast-track appointments for patients with suspected lung cancer and improved patient satisfaction and patient-rated quality of care for patients with low risk lung nodules. The new service is currently delivered solely by consultants and this may have impacted on the survey results.